Evaluating face gender cues in virtual humans within and beyond the gender binary - Ghosh, Rashi; Feijóo-García, Pedro Guillermo; Stuart, Jacob; Wrenn, Chase; Lok, Benjamin (Frontiers in Virtual Reality, 2023)
Virtual human work regarding gender is widely based on binary gender despite recent understandings of gender extending beyond female and male. Additionally, gender stereotypes and biases may be present in virtual human design. This study evaluates how face gender cues are implemented in virtual humans by conducting an exploratory study where an undergraduate computing population (N=67) designed three virtual human faces -female, male, and nonbinary.Results showed that face gender cues were implemented in stereotypical ways to represent binary genders (female and male virtual humans). For nonbinary gender virtual humans, stereotypical face gender cues were expressed inconsistently (sometimes feminine, sometimes masculine), and conflicting gender cues (pairs of cues that signal opposing binary gender) occurred frequently.Finally, results revealed that not all face gender cues are leveraged equally to express gender.Implications of these findings and future directions for inclusive and representative gender expression in virtual humans are discussed.